A narrative review of the high-carbohydrate fueling revolution (>=100 g/h) in the professional peloton - Wilson, P. B. (Sports Medicine, 2026)
High-carbohydrate fueling in cycling (defined as = 100 g/h for this paper) has received significant media attention in recent years. Whether this practice improves performance, however, remains an unresolved issue in the scientific literature. The purpose of this narrative review is to provide an up-to-date analysis of the practice of high-carbohydrate fueling, with a specific focus on potential performance implications in professional cycling. Topics covered include historical carbohydrate intake guidelines, research directly comparing high-carbohydrate fueling with traditional fueling guidelines, theorized benefits of high-carbohydrate fueling specific to cycling, potential risks associated with high-carbohydrate fueling, and personalizing carbohydrate intakes. Among a small number of experimental studies that have compared high-carbohydrate fueling with somewhat lower rates (e.g., 60-90 g/h), there is not clear evidence that it reduces reliance on endogenous carbohydrate stores or improves performance. However, these studies have not closely mimicked the demands of multi-day and multi-week stage races, when ingesting carbohydrate at = 100 g/h may be more likely to produce performance benefits. Observational data from professional cyclists suggest that carbohydrate consumption during racing is strongly associated with total daily carbohydrate intakes; therefore, ingesting carbohydrate at = 100 g/h on the bike could facilitate performance over multiple days or weeks by enhancing glycogen resynthesis and recovery. In addition, circumstantial evidence suggests that high-carbohydrate fueling could reduce low energy availability, reduce within-day energy deficits, and stimulate the central nervous system. Personalizing carbohydrate intakes through individual assessments of exogenous carbohydrate oxidation is a novel strategy that should be further explored in the future.